The Utilization of Digital Technology for English Literacy Improvement in Islamic Senior High Schools - Suadi, Suadi; Siregar , Ayu Meita Puteri; Arwin, Arwin; Majid, Ikhwanuddin Abdul (International Journal of Social Learning (IJSL), 2025)
The utilization of digital technology is perceived as significant in the English learning process. This research aimed to investigate the utilization of digital technology for English literacy improvement among Class XII Islamic senior high school students. A mixed-method approach was applied by involving 60 students with purposive sampling. The results showed that Islamic senior high school students (Madrasah aliyah) spent an average of 1 to 3 hours a day using digital technology platforms, used YouTube the most frequently, trained their English by singing along to videos accessed from digital technology platforms, and used digital technology in an autodidactic manner. Contradictorily, most respondents claimed they seldom utilized digital technology for English-language content conversation. Moreover, the result revealed six benefits of adopting digital technology for English language literacy, compared to 6 drawbacks. The conclusion is that digital technology is relevant for English learning.